Categorisation frameworks in Termontography - Kerremans, Koen (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
The content of a terminology base should be determined by the purpose(s) for which it will be used as well as the profile(s) of its potential users. In this view, each terminological project first re quires defining what will be considered a term. In this article, we reflect on how – in the Termontography approach – requirements for multilingual terminology bases can be translated into frameworks of interrelated categories. These frameworks are templates for the extraction of terms and knowledge rich contexts from texts and will gradually evolve towards enriched and more fine-grained networks of semantic relations as the knowledge elicited from these texts is mapped to it. The implications of categorisation frameworks for methods in multilingual terminology description will be illustrated by frameworks set up in the FF POIROT and OMTOFIR research projects.